2003
DOI: 10.1186/ar1022
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte response to growth factors is modulated by p38 mitogen-activated protein kinase inhibition

Abstract: Inhibitors of p38 mitogen-activated protein kinase (MAPK) diminish inflammatory arthritis in experimental animals. This may be effected by diminishing the production of inflammatory mediators, but this kinase is also part of the IL-1 signal pathway in articular chondrocytes. We determined the effect of p38 MAPK inhibition on proliferative and synthetic responses of lapine chondrocytes, cartilage, and synovial fibroblasts under basal and IL-1-activated conditions.Basal and growth factor-stimulated proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“… 31 , 32 On the other hand, growth factors, such as TGF-β and insulin-like growth factor (IGF) modulate chondrocyte proliferation via inhibition of p38 MAPK and upregulation of ERK signaling. 33 Our study showed similar results where exposure of chondrocytes to IL-1β significantly increased expression of proinflammatory cytokines, NO, and p38 MAPK. However, treatment of cells with herbals, in particularly C. quadrangularis and the combination therapy, considerably alleviated production of catabolic agents by inhibiting activation of p38 MAPK and ERK2 signaling.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“… 31 , 32 On the other hand, growth factors, such as TGF-β and insulin-like growth factor (IGF) modulate chondrocyte proliferation via inhibition of p38 MAPK and upregulation of ERK signaling. 33 Our study showed similar results where exposure of chondrocytes to IL-1β significantly increased expression of proinflammatory cytokines, NO, and p38 MAPK. However, treatment of cells with herbals, in particularly C. quadrangularis and the combination therapy, considerably alleviated production of catabolic agents by inhibiting activation of p38 MAPK and ERK2 signaling.…”
Section: Discussionsupporting
confidence: 81%
“…This in turn leads to inflammation, further cytokine production, osteoclast differentiation, and chondrocyte apoptosis 31,32. On the other hand, growth factors, such as TGF-β and insulin-like growth factor (IGF) modulate chondrocyte proliferation via inhibition of p38 MAPK and upregulation of ERK signaling 33. Our study showed similar results where exposure of chondrocytes to IL-1β significantly increased expression of proinflammatory cytokines, NO, and p38 MAPK.…”
Section: Discussionsupporting
confidence: 73%
“…In particular, it has been shown that high serum levels of IL-6 may associate with the development of AS [ 36 ]. The triggering of mitogen-activated kinase (MAPK) signaling cascade leads to activation of downstream JUN N-terminal kinase (JNK) and p38/MAPK14 [ 37 ], which is involved in the proinflammatory activity of interleukin 1 (IL-1) and TNF-alpha [ 38 ]. The transcript for this kinase was 1.8 fold increased in AS samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transforming growth factor-␤-induced aggrecan transcription in ATDC5 chondrogenic cells requires ERK1/2 and p38 activation (42). In addition, p38 signaling contributes toward transforming growth factor-␤-stimulated proteoglycan synthesis and chondrocyte proliferation (36,37), and ERK1/2 is activated by insulin-like growth factor-1, which strongly promotes anabolic chondrocyte behavior (17,35). It was also shown recently that JNK inhibition during cyclic compression of tissue-engineered constructs prevents up-regulation of aggrecan and type II collagen, as well as MMP3 and MMP13 genes (51).…”
Section: Discussionmentioning
confidence: 99%